The sozological and hygrographic maps of Poland as a basis for the analysis of environmental changes in mining areas = Sozologiczne i hydrograficzne mapy Polski jako podstawa do analizy zmian środowiska na terenach górniczych - Fagiewicz, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the forthcoming decades large resources of lignite are going to play a role of energy security stabiliser in Poland. This proves the significance of the problems of mining areas in geographical space and entails an increased demand for data on their structure and functioning.
Keywords: mapy sozologiczne; mapy hydrograficzne; tereny pogórnicze; węgiel brunatny; thematic databases; geographic information system (GIS); mining and post-mining areas